2022
DOI: 10.1002/cnr2.1713
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in melanoma incidence and mortality in rural versus urban Michigan

Abstract: Introduction: We sought to identifying the possible existence of disparities between rural and urban residents of Michigan for the incidence by stage of disease and disease-specific mortality for cutaneous melanoma (CM). Methods: Incidence rates for stage of disease and disease-specific mortality of cutaneous melanoma were calculated and controlled for gender, age, and area of residence from January 1, 2014, to December 31, 2018, from data collected form the Michigan Department of Health and Human Services and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several prior studies have reached similar findings concerning cause-specific mortality and rurality, without identifying access to care as a potential cause. Shellenberger et al 9 found both higher incidence and cause-specific mortality rates in rural versus urban Michigan counties. These findings were not correlated with differences in the number of practicing dermatologists per county or likely associated with differences in stage at presentation because even localized stage presentation differed significantly between rural and urban locations; the authors hypothesized that an inability to use race and/or insurance status as a covariate may have contributed to the observed patterns.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several prior studies have reached similar findings concerning cause-specific mortality and rurality, without identifying access to care as a potential cause. Shellenberger et al 9 found both higher incidence and cause-specific mortality rates in rural versus urban Michigan counties. These findings were not correlated with differences in the number of practicing dermatologists per county or likely associated with differences in stage at presentation because even localized stage presentation differed significantly between rural and urban locations; the authors hypothesized that an inability to use race and/or insurance status as a covariate may have contributed to the observed patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Henley et al 8 found higher incidence rates for melanoma in nonmetropolitan rural counties across the United States and higher cause-specific death rates in nonmetropolitan versus metropolitan counties overall. Shellenberger et al 9 found both incidence rates and cause-specific mortality rates for cutaneous melanoma to be significantly greater in rural Michigan counties. Alternatively, Haluza et al 10 found significantly higher melanoma incidence and cause-specific mortality rates in urban districts in Austria, yet somewhat conflicting patterns with respect to altitude.…”
mentioning
confidence: 99%
“…Research has shown that rurality is associated with higher age‐adjusted melanoma incidence rate and melanoma‐specific mortality rates, particularly in men. 1 , 2 , 3 Twenty‐two percent of Indiana residents live in counties with rural designations, and it is estimated that 2180 cases of melanoma will be diagnosed in Indiana in 2023. 4 , 5 To establish equitable care, it is imperative to identify and address associations between rurality and melanoma disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…12 When looking at patients with CM specifically, rural populations often have greater age-adjusted incidence rates 13 and melanoma-specific mortality rates. 14 Patients living in rural areas are more likely to experience delays in receiving a biopsy and have biopsies performed by primary care physicians, 15 when studies have shown that dermatologists detect CM at thinner depths and earlier stages. 16,17 In addition, patients with melanoma detected by a dermatologist are less likely to experience delays in surgery compared to a non-dermatologist provider 18 ; however, rural regions have decreased densities of dermatologists.…”
Section: Introductionmentioning
confidence: 99%
“…18 Additionally, those studies that did investigate rurality are in smaller, regional cohorts, or did not account for treatment receipt. 14 However, there is a gap in the literature on how geography directly impacts CM treatment receipt and survival. Therefore, we aimed to assess the association between rurality and receipt of recommended surgery and melanoma cause-specific mortality in a national cohort.…”
Section: Introductionmentioning
confidence: 99%